DIGITAL PMMA, WHEN AND WHICH - Andreea Mariana Bănățeanu; Cristian Niky Cumpătă; Alexandru Burcea (Romanian Journal of Oral Rehabilitation)
Polymethyl methacrylate (PMMA) has become a cornerstone of dental prosthetics, valued for its adaptability, biocompatibility, and cost-effectiveness. In recent years, rapid advancements in material science and digital manufacturing technologies, particularly CAD/CAM milling and 3D printing, have driven PMMA to new levels of functionality and application. These innovations have enhanced the material’s physical properties—such as strength, aesthetic quality, and wear resistance—making it suitable for both temporary and, in some cases, long-term dental restorations. This review examines the evolution of PMMA in dental applications, emphasizing recent modifications in material composition, digital processing techniques, and clinical outcomes. Topics covered include multi-layered and high-impact PMMA variants, milling advancements, 3D printing methods, and how these developments address clinical needs in modern dentistry.